Multisensor Railway Track Geometry Surveying System - Akpinar, Burak; Gulal, Engin (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
Linear variable differential transformers (LVDTs) and inclinometers are widely used in many industrial establishments, particularly in the metrology area. These sensors are used by many engineering disciplines because of their high-precision characteristics. In addition, Global Navigation Satellite System (GNSS) receivers and total stations are widely used in geodesy. Using GNSS receivers is very popular, particularly for navigational purposes. In this paper, a new railway track geometry surveying system, which is designed by integrating the LVDT, inclinometer, GNSS receiver, and total station, is introduced. This new surveying system is an alternative to classical geodetic measurement methods that are often used for controlling the railway track geometry. Track gauge, super-elevation, gradient, and track axis coordinates, which are railway geometrical parameters, can be instantly determined while making measurements by using the new surveying system.
Keywords: Geodesy; Global Positioning System; multisensor systems; rail transportation maintenance; NAVIGATION; Engineering; Instruments & Instrumentation